Analisis Faktor-Faktor Yang Mempengaruhi Produksi Sektor Pertanian Di Propinsi Aceh - Hermansyah Putra; Muhammad Nasir (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2015)
ABSTRACT. This study aims to determine the factors that affect the production of the agricultural sector in the Aceh province. Furthermore, these factors can determine the level of production growth in the agricultural sector in the GDP of Aceh can be analyzed properly. The data used in this research is secondary data are time series from 1985 to 2013. The analysis model used is multiple linear regression model (multiple regression) were estimated by Ordinary Least Square method (OLS). The results showed that the variable labor, Domestic Investment (DCI), and the land area and a significant positive effect on the production of the agricultural sector in Aceh province. Based on these results, it is suggested to the government in order to maintain the stability of the economy in the Aceh province to implement a policy that is relevant. Thus, factors that affect for agricultural production growth in GDP at Aceh province could be optimized.